Bold, bright, beautiful. (2nd April 2021) - Harries, Judith
Abstract : Introduce children to the award-winning author and illustrator Lois Ehlert and equip them to create colourful collages with a range of resources including coloured paper, glue, wire, thread and recycled textiles.